An unusual presentation of chronic lymphocytic leukemia - Dinesh Atwal (Thieme Medical and Scientific Publishers Pvt. Ltd., 2017)
Chronic lymphocytic leukemia/small lymphocytic lymphoma (CLL/SLL) is a B-cell lymphocytic neoplasm with indolent clinical course. If identified early, observation is opted. Many variables lead to the initiation of treatment. Authors describe a 62-year-old male presenting with shortness of breath and found to have white cell count of 1360 × 109/L and subsequently was diagnosed with CLL/SLL. The patient received leukapheresis along with tumor lysis treatment and systemic chemotherapy with fludarabine, cyclophosphamide, and rituximab regimen. His course was complicated with deep venous thrombosis, extensive cutaneous, and sinus mucosa involvement by CLL/SLL. The patient clinically improved and on follow-up clinic visits documented normalization of his white cell counts. The case report brings up a rare presentation of CLL/SLL with such an extreme high white cell count, leukostasis symptoms and extramedullary involvement of disease and encourages providers to be vigilant of rare presentation of CLL/SLL.